(untitled) (Journal of Social Sciences Review, 2023)
The article provides an assessment of the current and future international laws regarding global health governance with a focus on outbreak reporting. The article highlights the flaws of the existing system and the need for a sustainable One Health approach to be incorporated into any proposed modifications to international law, such as a pandemic treaty or new global health rules. The authors emphasize how a treaty may increase reporting requirements, accelerate the exchange of scientific discoveries, and enhance existing legal institutions while resolving the most complex problems currently facing international health governance. The article concludes by highlighting the potential for international law reform to develop a framework for global health that enables successful information sharing regardless of the emergency.